Semitic paronomasia in Mark; the Son of Man illuminated - Ballentyne, Stephen (2024)
Twentieth century scholarship carefully sampled the Semitic flavour of the gospels. Pioneers like Matthew Black, J.K. Elliott and Maurice Casey observed and analysed countless Semitisms of syntax, grammar, phrasing and literary device in the New Testament. In the Hebrew Bible, others identified and analysed poetic conventions such as Janus parallelism, a punning device that features with particular frequency in the Book of Job. But seldom did studies explore the emergence of poetic paronomasia in the New Testament, whether ostensibly replicated in Greek or apparent only after reconstructing a Hebrew or Aramaic Vorlage. Janus parallelism has enjoyed considerable attention among Hebrew Bible scholars since Cyrus Gordon’s breakthrough work in 1978, yet hitherto no Janus research has been published with an eye on the New Testament. Name-puns have likewise been treated lightly. Further, though literature exists on Aramaic gospel reconstructions, scholars have almost universally ignored Hebrew’s potential. Few scholars have attempted to engage with Carmignac, or the work of such moderate Hebraists as Kutscher, who support at least the possibility of Hebrew templates for parts of the gospels. Scholarly silence lingers over such findings, silence this thesis attempts to shatter, as I assess Carmignac’s work on Hebrew paronomasia in Mark, design and implement a methodology for assessing Hebrew/Aramaic reconstructions of Janus parallelism, and analyse over a dozen newfound cases of Semitic Marcan punning, including parallelism, that I have discovered. This thesis will show that hidden layers of meaning, especially irony, often emerge when we reconstruct Semitic templates for Marcan lexemes, layers largely untapped by New Testament exegetes. We shall further address whether these meanings were likely intentional, or products of coincidence, deducing that parts of Mark’s gospel must indeed have been translated from Semitic Vorlagen. I shall conclude that, in future scholarship, a place should be reinstated for Hebrew gospel reconstruction.